Matters of life and death : psychoanalytic reflections - Akhtar, Salman, 1946 July 31- (Karnac, 2011)
The author's focus in this book is upon the intrapsychic vicissitudes of what it means to be truly alive and how death accompanies us at each step of our life's journey. He attempts to show that, psychologically-speaking, death is always present in life and life in death. He discovers what is emotionally central to being alive and how death and awareness of death - conscious or unconscious - silently color our subjective experience. The fundamental thrust of these socio-clinical meditations is to enhance appreciation of aspects of life that have been inoptimally addressed in psychoanalytic lit.